SIFAT FISIK DAGING AYAM PETELUR AFKIR YANG DIRENDAM DALAM EKSTRAK KULIT NENAS (Ananas comosus L. Merr) DENGAN KONSENTRASI YANG BERBEDA - Endah Purnamasari; Muhammad Zulfahmi; Irdha Mirdhayati (State Islamic University of Sultan Syarif Kasim Riau, 2012)
The aims of this study were to determine the effect of immersing culled layer chicken meat into the pineapple skinextract with different concentrations on the water holding capacity (WHC), water content (WC), pH, tenderness, odor andcolor. The experimental design was Completely Randomized Design (CRD) with four replications. Treatments wereconcentrations of pineapple skin extract which consisted of four levels that is 0%, 15%, 27,5% and 40%, respectively.Results showed that immersion of culled layer chicken meat into the pineapple skin extract had significant effect (P<0,01) onWHC, pH, tenderness. The concentration of 27,5% of pineapple skin extract could increase tenderness, decreased WHC andpH.